METAPHORICAL-FUNCTIONAL ANALYSIS OF ARABIC LOANWORDS IN “THE STORIES OF THE PROPHETS” BY RABGHUZI - Sagdullaeva Dilfuza Karimullaevna (Western European Studies, 2025)
This article deals with lexical-semantic and metaphorical-functional analysis of the content of Arabic loanwords in the “The Stories of the Prophets” by Nosiruddin Burhonuddin Rabghuzi, being primarily published in Turkic language based on Islamic sources, from the viewpoint of Arabic science of balāǧat which was included into the sciences of Qur’ān in Middle Ages and issues that involve the science of balāǧat – rules and methods of expressing the sentence by various means in order to interpret and explain the purpose are studied in the science of bayān
Keywords: arabic loanwords; science of balāǧat; lexical-semantic analysis